2014
DOI: 10.1177/1468794114538897
|View full text |Cite
|
Sign up to set email alerts
|

Catching the shimmers of the social: from the limits of reflexivity to methodological creativity

Abstract: With the questioning of the neutral objective researcher, reflexivity has jumped to the forefront of qualitative research, thus positioning the embodied researcher within the research process. In its power to reveal tacit embodied social structures, reflexivity is touted as the hallmark of methodological validation while also being described as a messy process, particularly in participatory research. In this article, we use illustrative examples from our participatory research exploring the healing practices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
2
31
0
1
Order By: Relevance
“…Indeed, this researcher's social position (in particular race and nationality) was a considerable factor (in encouraging the women to take part) over and above any empathetic emotional bond felt by the respondent for the investigator's personal familiarity with the subject. This consequence from the investigation supports Hibbert et al (2010) who acknowledge the limitations of the reflexive process and posit reflexivity should only be used to convey cultural meaning to the reader or to gain deeper insight into the field of research otherwise there is a risk of messy methodological processes (Kumsa et al, 2015).…”
Section: Conclusion and Recommendationssupporting
confidence: 61%
See 1 more Smart Citation
“…Indeed, this researcher's social position (in particular race and nationality) was a considerable factor (in encouraging the women to take part) over and above any empathetic emotional bond felt by the respondent for the investigator's personal familiarity with the subject. This consequence from the investigation supports Hibbert et al (2010) who acknowledge the limitations of the reflexive process and posit reflexivity should only be used to convey cultural meaning to the reader or to gain deeper insight into the field of research otherwise there is a risk of messy methodological processes (Kumsa et al, 2015).…”
Section: Conclusion and Recommendationssupporting
confidence: 61%
“…Reflexivity has raced to the forefront of qualitative research because of the unique position of the neutral objective researcher (Kumsa et al, 2015). There is a considerable body of literature on reflexivity in the development of management literature, whereby the demands for reflexive writing are discussed because of the benefit it provides to researchers (Van Maanen, 2006;Mahadevan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This moves away from researcher as "disembodied voice" (Bolwell, 2011, p. 686) and places me firmly within the field with authentic lived experience as the mindfulness practice through yoga is implicitly embodied. Subjectivities of the researcher in this work are integral to the analysis of the data (Kumsa, Chambon, Yan, & Maiter, 2015;Pillow, 2003). I am not gathering separate pieces of information, but instead, examine inter-related stories which allow the discovery of themes that are the starting point of the inquiry (Todres & Holloway, 2010) as a self-reflexive practitioner.…”
Section: Reflexivity As a Creative Methodologymentioning
confidence: 99%
“…Third objects implemented in this research study aided in evoking discussions about personal parental and sensitive issues, including race and discrimination. Although researchers have explored experiences of racism using objects and video (Kumsa et al, 2015;Maiter et al, 2013), it is suggested that no similar tool has been implemented to explore sensitive issues with BACM in elite institutions. Using a CRT lens with third object prompts to examine BACM experiences is a way of raising awareness of sensitive issues that may lead to environmental improvement in academic spaces.…”
Section: Discussionmentioning
confidence: 99%